Chinese linkage, leverage, and Cambodia's transition to hegemonic authoritarianism. Issue 4 (19th May 2021) - Loughlin, Neil
ABSTRACT: This article considers authoritarian linkage politics and its relationship to regime stability. Between 2012 and 2018, Cambodia experienced its worst political crisis in a decade. During this period, China's economic assistance, diplomatic backing and military exchanges have cemented it as the ruling Cambodian People's Party's (CPP) most important foreign partner. This article's findings support the linkage thesis: that ties between authoritarian regimes enhance their survival in moments of crisis. The article provides evidence for the specific forms of linkages that proved vital to the CPP during a transition from competitive to hegemonic authoritarianism. It shows that alongside more familiar linkage ties, the CPP also drew on more diffuse types of authoritarian cooperation and emulation, while Chinese discourses on non-interference and the right to develop provided an authoritarian nexus supporting CPP legitimation narratives in defiance of challengers. The article reflects on Cambodia's variant of hegemonic authoritarianism in light of these observations. Finally, the argument draws attention to leverage exercised on Cambodia by China as a consequence of these linkages, which have been beneficial to China's strategic and military interests in Southeast Asia. In the current moment of autocratization and great power competition globally, this has implications for research beyond Cambodia.